Sound advice : becoming a better children's choir conductor - Bartle, Jean Ashworth (Oxford University Press, 2003)
Always a vital part of community cultural life, children's choirs can be small amateur clubs or sophisticated arts organizations on a par with adult professional choirs and orchestras. Whatever a choir's size and ambitions, its director faces a formidable challenge. Jean Ashworth Bartle, director of the award-winning Toronto Children's Chorus, has collected her experience and wisdom in Sound Advice. In a clear and direct style, the book offers tips on basics such as conducting fun, effective rehearsals and advanced projects including recording and touring. Stressing that the choir director's fundamental task is to develop musicianship through singing, Bartle suggests skill-building exercises and interactive rehearsal techniques. The book's appendixes form a sourcebook of warm-ups, repertoire, and suggested programmes, providing several seasons' worth of inspiration. For teachers just starting out with their choirs, students of the child voice and teaching methods, and experienced choir directors seeking to take their students one step further, Sound Advice will benefit all choir directors who want their choirs to reach a higher level of artistry, musicianship and skill.